Individualized Instruction, Cooperative Learning Strategy and Reading Performance of Adult Learners in Selected Study Centres in Ibadan - Fagbemi , Olusegun Olujide; Akinsola, Olutayo Olaniyi (Interdisciplinary Journal Of Lifelong Learning, 2025)
This study explored the effectiveness of individualized instruction and cooperative learning strategy in enhancing the reading performance of adult learners in selected study centres in Ibadan. A quasi-experimental design with three groups (individualized instruction, cooperative learning, and a control group) was used. Participants were 45 first-grade adult learners with reading difficulty identified with the help of instructors and selected using purposive sampling technique. The selection was made across 3 study centres within Ibadan. Reading Comprehension Achievement Test (RECAT; reliability coefficient = 0.71) was used to assess the reading comprehension of the participants for pretest and post-test. Findings showed a statistically significant improvement in reading comprehension for both individualized instruction (Xˉ=42.7, SD=6.8,t=10.77,p<0.05) and cooperative learning (Xˉ=39.4,SD=2.84,t=10.04,p<0.05) groups compared to the control group (Xˉ=30.3,SD=3.5 and Xˉ=33.3,SD=3.51 respectively). In addition, individualized instruction (Xˉ=42.67,SD=2.6) demonstrated higher reading comprehension scores than cooperative learning (Xˉ=39.47,SD=2.8,t=3.21,p<0.05). These findings reveal the efficacy of both strategies in enhancing adult literacy, with individualized instruction demonstrating a stronger impact than the other method. The study recommends two learner-centred approaches be integrated into adult literacy programmes and continuous training and capacity building for adult instructors to effectively implement them.